The logarithmic function is the inverse of the exponential function
The logarithmic equivalent of the exponential function is log(12) = [tex]\frac 43[/tex]log(x) + log(y) + 2log(z)
The exponential function is given as:
12^3=x^4 y^3 z^6
Take the logarithm of both sides
log(12^3) =log(x^4 y^3 z^6)
Apply the product rule of logarithm
log(12^3) =log(x^4) + log(y^3) + log(z^6)
Apply the power rule of logarithm
3log(12) = 4log(x) + 3log(y) + 6log(z)
Divide through by 3
log(12) = [tex]\frac 43[/tex]log(x) + log(y) + 2log(z)
Hence, the logarithmic equivalent of the exponential function is log(12) = [tex]\frac 43[/tex]log(x) + log(y) + 2log(z)
Read more about logarithms and exponential functions at:
https://brainly.com/question/7988782